2009
DOI: 10.1128/jvi.01768-08
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of mda-5 Inhibition by Paramyxovirus V Proteins

Abstract: The RNA helicases encoded by melanoma differentiation-associated gene 5 (mda-5) and retinoic acidinducible gene I (RIG-I) detect foreign cytoplasmic RNA molecules generated during the course of a virus infection, and their activation leads to induction of type I interferon synthesis. Paramyxoviruses limit the amount of interferon produced by infected cells through the action of their V protein, which binds to and inhibits mda-5. Here we show that activation of both mda-5 and RIG-I by double-stranded RNA (dsRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
138
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(146 citation statements)
references
References 34 publications
8
138
0
Order By: Relevance
“…Accordingly, we found that the MV V protein interacted with MDA5 via the cysteine-rich region. Childs et al (2009) reported that the V protein of paramyxovirus specifically inhibited activation of the MDA5 pathway, but not the RIG-I pathway, by specifically binding to the helicase domain of MDA5 and hindering MDA5 from recruiting dsRNA. Consistent with their report, the V protein thus blocks sensing dsRNA via MDA5 to disassemble oligomerization of MDA5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, we found that the MV V protein interacted with MDA5 via the cysteine-rich region. Childs et al (2009) reported that the V protein of paramyxovirus specifically inhibited activation of the MDA5 pathway, but not the RIG-I pathway, by specifically binding to the helicase domain of MDA5 and hindering MDA5 from recruiting dsRNA. Consistent with their report, the V protein thus blocks sensing dsRNA via MDA5 to disassemble oligomerization of MDA5.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the 272C residue is crucial for the V protein to block MDA5 function and MDA5 is the molecule which V protein targets for inhibition of the initial induction of IFN-E. For this reason, the ED strain used in this study allowed infected cells to induce IFN-E mRNA even in the absence of DI RNA. A previous report showed that the V protein of Sendai virus binds MDA5 via the cysteine-rich region which is conserved among paramyxoviruses (Childs et al, 2009). Accordingly, we found that the MV V protein interacted with MDA5 via the cysteine-rich region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 The V proteins of paramyxoviruses interact with MDA-5 to block its activity, which leads to a reduction in IFN-b promoter activation. 20 The cysteine protease NS3/4A of hepatitis C virus cleaves VISA and the TLR3 adapter protein TRIF, thereby blocking RIG-I-and TLR3-mediated induction of the type I IFNs. 21,22 The A52 and A46 proteins of vaccinia virus target multiple TIR proteins, including TRIF, to block TLR3-and TLR4-mediated induction of type I IFNs.…”
Section: Introductionmentioning
confidence: 99%
“…The V proteins of at least 13 paramyxoviruses tested bind to MDA5 to inhibit IFN induction [32,[69][70][71] . Rinderpest virus (RPV) may differ, as it appears to use the C protein rather than V to inhibit MDA5 signalling, although the binding of RPV V to MDA5 has not been examined [72] .…”
Section: Targeting Of Mda5mentioning
confidence: 99%